Flora used other than Medicinal purposes by Baduga ethnic in Nilgiri. (International Journal of Scientific Research and Management (IJSRM), 2016)
An ethno-botanical study, particularly the plants used other than medicinal purposes was carried out among the Baduga community in Nilgiri hills of Tamil Nadu, India during November 2014 to April 2015. Uses of 24 non medicinal plant species spread over 20 families are described under this study.Mostly these plants were used as food, religious purposes, festives, decorative purposes, as insect repellents,biofertilizers, construction purposes, making household implements, agriculture implements and fuel. The study showed a high degree of ethno-botanical novelty and the use of plants among the Nilgiri tribals.